Differential Expression of Drosophila Transgelins Throughout Development - Vakaloglou, Katerina M.; Mouratidou, Maria; Keramidioti, Athina; Zervas, Christos G. (Frontiers in Cell and Developmental Biology, 2021)
Transgelins is a conserved family of actin-binding proteins involved in cytoskeletal remodelling, cell contractility and cell shape. In both mammals and Drosophila three genes encode transgelin proteins. Transgelins exhibit a broad and overlapping expression pattern, which has obscured the precise identification of their role in development. Here, we report the first systematic developmental analysis of all Drosophila transgelin proteins, namely Mp20, CG5023 and Chd64 in the living organism. Drosophila transgelins display overall higher sequence identity with mammalians TAGLN-3 and TAGLN -2 than with TAGLN. Detailed examination in different developmental stages revealed that Mp20 and CG5023 are predominantly expressed in mesodermal tissues with the onset of myogenesis and accumulate in the cytoplasm of all somatic muscles and heart in the late embryo. Notably, at post-embryonic developmental stages, Mp20 and CG5023 are detected in the gut's circumferential muscles with distinct subcellular localization: Z-lines for Mp20, sarcomere and nucleus for CG5023. Only CG5023 is strongly detected in the adult fly in the abdominal, leg and synchronous thoracic muscles. Chd64 protein is primarily expressed in endodermal and ectodermal tissues and have a dual subcellular localization in the cytoplasm and the nucleus. During the larval-pupae transition, Chd64 is expressed in brain, eye, legs, halters and wings. In contrast, in the adult fly, Chd64 is expressed in epithelia, including the alimentary tract and genitalia. Based on the non-overlapping tissue expression, we predict that Mp20 and CG5023 mostly cooperate to modulate muscle function, whereas Chd64 has distinct roles in epithelial, neuronal and endodermal tissues.